2020
DOI: 10.48550/arxiv.2011.06857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hyperon electromagnetic form factors in the timelike region

Johann Haidenbauer,
Ulf-G. Meißner,
Ling-Yun Dai

Abstract: Electromagnetic form factors of hyperons (Λ, Σ, Ξ) in the timelike region, accessible in the reaction e + e − → Ȳ Y , are studied. The focus is on energies close to the reaction thresholds, where the properties of these form factors are significantly influenced by the interaction in the final Ȳ Y system. This interaction is taken into account in the calculation, utilizing Ȳ Y potential models that have been constructed by the Jülich group for the analysis of data from the reaction pp → Ȳ Y in the past. The enh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…This may indicated that there should be also other contributions around that energy region. For example, the electromagnetic form factors should be significantly influenced by the interaction in the final Σ + Σ − system [5]. However, since the experimental data are so limited, and we will leave those contributions to further study when more precise data are available.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may indicated that there should be also other contributions around that energy region. For example, the electromagnetic form factors should be significantly influenced by the interaction in the final Σ + Σ − system [5]. However, since the experimental data are so limited, and we will leave those contributions to further study when more precise data are available.…”
Section: Numerical Results and Discussionmentioning
confidence: 99%
“…The study of the structure of hyperons which contain strange quark through their electromagnetic form factors (EMFFs) is crucial for deep understanding the nonperturbative quantum chromodynamics (QCD) effects that quarks are bounded in baryons [1][2][3][4][5]. As discussed in Refs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last two decades, the EMFFs of hyperons (i.e., Λ, Σ, Ξ) in the time-like region have also been investigated. Particularly, the enhancement of the cross sections in reactions e + e − → Y Ȳ near threshold were measured and analyzed [20][21][22][23][24][25]. It is found that the vector mesons and their resonances, as the intermediate states of the reaction, play important roles in these processes.…”
Section: Introductionmentioning
confidence: 99%
“…The first theoretical estimates of the e + e − → B B cross sections and hyperon effective form factor, in the timelike region, were based on vector meson dominance (VMD) models [69,70]. More recently, with the emergence of accurate data for a variety of hyperons, new models have been proposed [6,[71][72][73][74], including improved VMD models [75][76][77][78][79][80]. Most of these studies focus on the Λ and Σ systems.…”
Section: Introductionmentioning
confidence: 99%